Analysis of the performance of the TRACHY score as a predictive factor for determining the need for elective tracheostomy in patients with head and neck malignancies undergoing extensive excision and reconstruction surgery at Dr. Soetomo General Regional - Agustina, Sisca Dwi; Wibowo, Marjono Dwi; Susilo, Dwi Hari (Edelweiss Applied Science and Technology, 2025)
Head and neck malignancies are the fifth most common type of cancer worldwide, and surgery has become the primary treatment for head and neck cancer. After major surgery in the head and neck region, the risk of upper airway obstruction is very high. This study aims to evaluate the TRACHY Score as a predictive factor for determining the need for elective tracheostomy in patients with head and neck malignancies who undergo extensive excision and reconstruction at Dr. Soetomo General Regional Hospital. This research is an analytical observational study with a retrospective cohort design, using secondary data in the form of medical records from patients with head and neck malignancies who underwent extensive excision and reconstruction at Dr. Soetomo General Regional Hospital from January 2020 to February 2024, and who met the inclusion and exclusion criteria. Clinical data from the TRACHY score parameters were analyzed, and comparisons were made between sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy in predicting the need for elective tracheostomy. A total of 34 study subjects were included, and 10 patients (29.4%) underwent tracheostomy. Using a cutoff score of 2, the sensitivity, specificity, PPV, NPV, and accuracy values for the TRACHY Score were found to be 100%, 66.6%, 55.5%, 100%, and 76.4%, respectively. The TRACHY Score demonstrates strong performance (including specificity, sensitivity, NPV, PPV, and accuracy) as a predictive tool for assessing the need for elective tracheostomy in patients with head and neck malignancies undergoing extensive excision and reconstruction surgery.